Mapping of Leaf Rust Resistance Genes and Molecular Characterization of the 2NS/2AS Translocation in the Wheat Cultivar Jagger. Issue 6 (1st June 2018) - Xue, Shulin; Kolmer, James A; Wang, Shuwen; Yan, Liuling
Abstract: Winter wheat cultivar 'Jagger' was recently found to have an alien chromosomal segment 2NS that has Lr37, a gene conferring resistance against leaf rust caused by Puccinia triticina . The objective of this study was to map and characterize the gene(s) for seedling leaf rust resistance in Jagger. The recombinant inbred line (RIL) population of Jagger × '2174' was inoculated with leaf rust pathogen THBJG and BBBDB, and evaluated for infection type (IT) response. A major quantitative trait locus (QTL) for THBJG and BBBDB was coincidently mapped to chromosome arm 2AS, and the QTL accounted for 56.6–66.2% of total phenotypic variation in infection type (IT) response to THBJG, and 72.1–86.9% to BBBDB. The causal gene for resistance to these rust races was mapped to the 2NS segment in Jagger. The 2NS segment was located in a region of approximately 27.8 Mb starting from the telomere of chromosome arm 2AS, based on the sequences of the A genome in tetraploid wheat. The Lr17a gene on chromosome arm 2AS was delimited to 3.1 Mb in the genomic region, which was orthologous to the 2NS segment. Therefore, the Lr37 gene in the 2NS segment can be pyramided with other effective resistance genes, rather than Lr17a in wheat, to improve resistance to rust diseases.